Mitochondrial quality control by the ubiquitin–proteasome system. (21st September 2011) - Taylor, Eric B.; Rutter, Jared
Abstract : Mitochondria perform multiple functions critical to the maintenance of cellular homoeostasis and their dysfunction leads to disease. Several lines of evidence suggest the presence of a MAD (mitochondria-associated degradation) pathway that regulates mitochondrial protein quality control. Internal mitochondrial proteins may be retrotranslocated to the OMM (outer mitochondrial membrane), multiple E3 ubiquitin ligases reside at the OMM and inhibition of the proteasome causes accumulation of ubiquitinated proteins at the OMM. Reminiscent of ERAD [ER (endoplasmic reticulum)-associated degradation], Cdc48 (cell division cycle 42)/p97 is recruited to stressed mitochondria, extracts ubiquitinated proteins from the OMM and presents ubiquitinated proteins to the proteasome for degradation. Recent research has provided mechanistic insights into the interaction of the UPS (ubiquitin–proteasome system) with the OMM. In yeast, Vms1 [VCP (valosin-containing protein) (p97)/Cdc48-associated mitochondrial-stress-responsive 1] protein recruits Cdc48/p97 to the OMM. In mammalian systems, the E3 ubiquitin ligase parkin regulates the recruitment of Cdc48/p97 to mitochondria, subsequent mitochondrial protein degradation and mitochondrial autophagy. Disruption of the Vms1 or parkin systems results in the hyper-accumulation of ubiquitinated proteins at mitochondria and subsequent mitochondrial dysfunction. The emerging MAD pathway is important for the maintenance of cellular and therefore organismal viability.